Norovirus: new developments and implications for travelers' diarrhea. Issue 1 (December 2015) - Simons, Mark; Pike, Brian; Hulseberg, Christine E.; Prouty, Michael; Swierczewski, Brett
Abstract Noroviruses are the leading cause of acute gastroenteritis in the United States and are responsible for at least 50 % of acute gastroenteritis outbreaks occurring worldwide each year. In addition, noroviruses have caused outbreaks on cruise ships, in nursing homes and hospitals, and in deployed military personnel, but its role in the etiology of travelers' diarrhea is not well defined. The aim of this review is to describe the role of noroviruses in travelers' diarrhea in terms of epidemiology, current diagnostics, treatment and vaccine development efforts. Studies have shown prevalence rates of noroviruses in travelers' diarrhea cases ranging from 10–65 %. It is likely that norovirus prevalence rates are highly underestimated in travelers' diarrhea due to rapid onset, short duration of the illness, limited availability of laboratory facilities, and the fact that most clinical laboratories lack the diagnostic capability to detect noroviruses in stool. Further, additional studies are needed to accurately determine the true prevalence rates of norovirus as an etiologic agent of diarrhea among travelers to different regions around the world. With the rapid progress in the development of a norovirus vaccine, travelers could serve as an ideal population for future norovirus clinical trials.